2020
DOI: 10.1093/clinchem/hvaa095
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Novel Liquid Biomarkers in Patients with Metastatic Castration-Resistant Prostate Cancer Treated with Enzalutamide: A Prospective Observational Study

Abstract: Background Several treatment options were recently added for metastatic castration-resistant prostate cancer (mCRPC). However, response to therapy is variable, and biomarkers that can guide treatment selection and response evaluation are lacking. Circulating RNAs are a promising source of biomarkers. We explored messenger RNAs (mRNAs), microRNAs (miRNAs), and long noncoding RNAs (lncRNAs) as potential biomarkers in liquid biopsies of patients with mCRPC treated with enzalutamide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…Nevertheless, several recent studies support their relevance by different methods. Benoist et al 83 identified hsa-miR-3687 as a novel prognostic marker for response in patients with castration-resistant prostate cancer treated with enzalutamide. This miRNA may also confer aggressiveness of oesophagus cancer through its target gene PGRMC2 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several recent studies support their relevance by different methods. Benoist et al 83 identified hsa-miR-3687 as a novel prognostic marker for response in patients with castration-resistant prostate cancer treated with enzalutamide. This miRNA may also confer aggressiveness of oesophagus cancer through its target gene PGRMC2 84 .…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of plasma/serum samples from 97 mCRPC patients, Lin et al (20) found that low levels of miR-21 correlated with a shorter OS following treatment with docetaxel. A recent analysis by Benoist et al of miRNAs in whole blood samples did not reveal significant differences in the levels of miR-21 or miR-141 in mCRPC patients treated with enzalutamide compared to healthy volunteers (21). However, miRNAs detected in whole blood samples will be predominantly represented by those contained in erythrocytes, platelets and leukocytes, which likely mask the contribution of circulating cell-free miRNAs.…”
Section: Discussionmentioning
confidence: 93%
“…Among these lncRNAs of the signature, some studies have shown that AC099850.3 is also used as an autophagy-related lncRNA signature model in hepatocellular carcinoma as well as oral and oropharyngeal squamous cell carcinoma [46,47]. Benoist GE et al revealed that patients with NAALADL2-AS2 high-expression showed a longer time to progression [48].…”
Section: Discussionmentioning
confidence: 99%